Statin Use and the Progression of Coronary Artery Calcification in CKD: Findings From the KNOW-CKD Study - Jihyun Yang; Kyu-Beck Lee; Hyang Kim; Soo Wan Kim; Yeong Hoon Kim; Su Ah Sung; Jayoun Kim; Kook-Hwan Oh; Ji Yong Jung; Young Youl Hyun (Kidney International Reports)
Introduction: Statin treatment can reduce the risk of cardiovascular disease (CVD). Paradoxically, previous studies have shown that the use of statin is associated with the progression coronary artery calcification (CAC), a well-known predictor of CVD, in individuals with preserved renal function or in patients on dialysis. However, little is known about the association in patients with predialysis chronic kidney disease (CKD). The aim of this study was to characterize the relationship between statin use and progression of CAC in a CKD cohort of Korean adults. Methods: We analyzed 1177 participants registered in the Korean Cohort Study for Outcome in Patients with Chronic Kidney Disease (KNOW-CKD) cohort. Coronary artery calcium score (CACS) was assessed using cardiac computed tomography at baseline and 4 years after enrollment. CAC progression was defined using the Sevrukov method. Statin users were defined as those who used statins for 50% or more of the follow-up period. Results: The median (interquartile range) of CACS was 0 (0–30.33), and 318 (44.2%) participants had CACS above 0 at baseline. There were 447 (38.0%) statin users and 730 (62.0%) statin nonusers. After 4 years, 374 patients (52.0%) demonstrated CAC progression, which was significantly more frequent in statin users than in statin nonusers (218 [58.3%] vs. 156 [41.7%], P < 0.001). The multivariate-adjusted odds ratio for CAC progression in statin users compared to statin nonusers was 1.78 (1.26–2.50). Conclusion: Statin use, significantly and independently, is associated with CAC progression in Korean patients with predialysis CKD. Further research is warranted to verify the prognosis of statin-related CAC progression.